2021
DOI: 10.21203/rs.3.rs-1016191/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

COVID-Inconfidentes: How did COVID-19 and home office influence the prevalence of leisure-time physical inactivity? An analysis of before and during the pandemic

Abstract: Background The COVID-19 pandemic has brought drastic changes to the lives of the global population. The restrictions imposed by government agencies impacted the daily lives of citizens, influencing several health behaviors, such as physical activity (PA). Thus, the present study aimed to assess the prevalence of physical inactivity (PI) and its associated factors before and during the COVID-19 pandemic. Methods A population-based household seroepidemiological survey was conducted in two Brazilian municipalit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 28 publications
1
0
0
Order By: Relevance
“…Spending time outside on a balcony or in a garden also has a positive influence on well-being ( 101 , 102 ). As in our study, Moura et al ( 103 ) observed that individuals in Brazil who worked from home during the pandemic were less likely to be physically inactive. Benefits of working from home include shorter travel times to work and more leisure time which can also be used for PA ( 104 ).…”
Section: Discussionsupporting
confidence: 81%
“…Spending time outside on a balcony or in a garden also has a positive influence on well-being ( 101 , 102 ). As in our study, Moura et al ( 103 ) observed that individuals in Brazil who worked from home during the pandemic were less likely to be physically inactive. Benefits of working from home include shorter travel times to work and more leisure time which can also be used for PA ( 104 ).…”
Section: Discussionsupporting
confidence: 81%